Nanoemulgel: A Smarter Topical Lipidic Emulsion-based Nanocarrier - Mandal, Suraj; Vishvakarma, Prabhakar (Indian Journal of Pharmaceutical Education and Research, 2023)
In the last few decades, researchers have put a lot of time and effort into making new pharmaceuticals. As a result, there are now a huge number of pharmacological chemicals that can be used to treat a wide range of diseases that are a problem for the healthcare system. More than 50% of these medications are classed as BCS (Biopharmaceutical Classification System) class II/IV, indicating that they have limited therapeutic value and are not further studied. In this way, it has been shown that lipoidal manufacturing is a good way to distribute these kinds of medicines. This suggests that a method based on nanotechnology has a lot of potential. Nanoemulgel, a gel composed of diverse nano-lipoidal compositions, has been shown to be an effective method for applying topical drugs. Nanoemulgel is an emulsion-based topical gel product. The correct gelling ingredient is added to emulsion globules made using high energy or low energy processes to form nanoemulgel. Nanoemulgels can be made from all kinds of polymeric polymers, surfactants, and fats that range in size from 5 nm to 500 nm. Nanoemulgel has several topical treatments for both short-term and long-term problems. The widespread use of nanoemulgel formulations of recently patented drugs in a variety of healthcare settings has once again shown that topical administration is better than other methods. Toxicological studies of the chemicals used in these formulations must, however, take into account how safe they are, since the way they are given has changed a lot.
Keywords: Nanoemulgel; Bioavailability; BCS class II and IV; Nanotechnology